Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelian Album Fisik (K-Pop) - Shinta Dewi, Ni Putu Sukma; Ngurah Gede, Anak Agung; Mashyuni, Ida Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Consumer decision making is a problem-solving approach to human activities aimed at purchasing goods or services to satisfy their wants and needs. In order for consumers to make purchasing decisions, they need to pay attention to the factors that influence their purchasing decisions. This study aims to determine the impact of price and product quality on e-commerce users' decision to purchase real Korean pop (K-Pop) albums. This type of research is quantitative. The population consists of consumers who purchase real K-Pop  albums from e-commerce users of the city of Denpasar. The number of samples is 91. The sampling technique is non-probability sampling with purposeful sampling. Methods of data collection by interviews, documents and questionnaires. Test the tool using a validity and reliability test. The data analysis technique used is classical hypothesis testing including: Normality test, multicollinearity test, and variance test. For multiple linear regression analysis using F&t and R² test. Partial price has a positive and significant impact on the purchase decision. Product quality has a positive and significant impact on purchasing decisions. Price and product quality simultaneously have a positive and significant impact on purchasing decisions. To ensure consumers' purchasing decisions, K-Pop physical album makers are expected to maintain  product prices and quality, while consumers are more cautious in their purchasing decisions. mine